PENERAPAN MANAJEMEN SUMBER DAYA MANUSIA (MSDM) UNGGUL BERBASIS KOMPETENSI DI SOCIETY 5.0 - Yanti, Clara (Jurnal Teknologi Pendidikan, 2021)
Digitization in human resource management can help companies modernize HR functions and give them a competitive advantage. At the same time, changing work styles and changing HR needs are necessary. The researcher aims to find out how to apply competency-based human resource management in the digital era. Researchers also explore the current key benefits and risks, and analyze their impact on the competence and role of HR Professionals. The qualitative research includes the analysis of secondary data describing the level of existing digital skills based on the reactions of more than 7,000 respondents from six EU member countries (Germany, Finland, UK, Portugal, Sweden and Slovakia). The results obtained indicate that the application of HR professionalism tends to be reluctant to adopt technology. The results also confirm the importance of digitization for human resources and the demand for digital skills in recent years